ACTIVE CONTROL OF HIGH-SPEED RAILWAY VEHICLE PANTOGRAPH CONSIDERING VERTICAL BODY VIBRATION - ABDULLAH, Mohd Azman; Ibrahim, Azhar; MICHITSUJI, Yohei; NAGAI, Masao (IAEME, 2013)
The current collection system consists of a pantograph placed on the roof top of a trains’ vehicle and overhead contact wire supported by evenly spaced vertical holders which supply the current to the pantograph from the electric power grid. Most of the pantographs produce averagely good performances at low and medium speeds, approximately less than 250 km/h. However, at higher speeds, the response of the pantographs is distorted. Thus the stability of the current collection is in peril. In addition, due to vertical vibration of the car body during high speed, contact force variation occurs between the pantograph and overhead wire. Therefore, it is necessary to maintain the contact between pantograph and overhead wire. In this study, the multi-body dynamics analysis is used to model the flexible body of overhead wire. An excitation experiment is performed in order to determine the parameters of pantograph. With consideration of vertical body vibration, an active pantograph control is developed to eliminate the effect of vibration to contact force, reduce the maximum peaks and avoid contact loss.